High-efficiency n-type silicon PERT bifacial solar cells with selective emitters and poly-Si based passivating contacts. (15th November 2019) - Ding, Don; Lu, Guilin; Li, Zhengping; Zhang, Yueheng; Shen, Wenzhong
Highlights: Top efficiency of 21.15% is reported on large-area n -PERT bifacial solar cells with front selective emitter and rear poly-Si based passivating contacts. Laser doping is performed to reduce carrier recombination on front borosilicate glass surface based on conventional B-diffusion p + emitter. Efficiency of 24.64% is predicted by optimizing not only the rear poly-Si based passivating contacts, but also the front emitter and Si substrate parameters. Abstract: Bifacial crystalline silicon (c-Si) solar cells have currently attracted much attention due to the front high-efficiency and additional gain of power generation from the back side. Here, we have presented n -type passivated emitter and rear totally-diffused ( n -PERT) bifacial c-Si solar cells featuring front selective emitter (SE) and polysilicon (poly-Si) based passivating contacts. The SE formation was scanned with laser doping based on front boron-diffusion p + emitter. The poly-Si based passivating contacts consisting of nano-layer SiOx of ~1.5 nm thickness grown with cost-effective nitric acid oxidation and phosphorus-doped polysilicon exhibited excellent passivation for high open-circuit voltage. We have successfully achieved the large-area (156 × 156 mm 2 ) n -PERT bifacial solar cells yielding top efficiency of 21.15%, together with a promising short-circuit current density of 40.40 mA/cm 2 . Theoretical calculation has further demonstrated that the optimal thickness of SiOx nano-layer will increase from 1.5 nm to 1.8 nm if the density of interface defect state decreases by one magnitude from 1 × 10 10 cm −2 /eV, and the cell efficiency can be improved up to 24.64% with open-circuit voltage over 0.720 V by optimizing the parameters of functional materials and interface layers. The present work has indicated that the commercialization of low-cost and high-efficiency n -PERT bifacial c-Si cells is possible due to the processes compatible with existing production lines.